Avaliação de vacinas contra brucelose bovina no Brasil - Karina Leite Miranda (2009)
The Brazilian Ministry of Agriculture, Livestock and Food Supply launched in 2001 the National Program on the Control and Eradication of Brucellosis and Tuberculosis (PNCEBT), in which vaccination is one of the most important tools to control brucellosis. Thus, the presentwork was idealized to study the vaccines approved by the PNCEBT in Brazil. In this context, the first objective was to evaluate the growth of B. abortus strains on media containing different inhibitor agents in order to differentiate the vaccine strains S19 and RB51 from challenge strainsand other Brazilian field isolates. With this study, we concluded that rifampicin, erythritol and thionin are good inhibitor agents for this differentiation. The second aim was to evaluate different strains of mice (CD-1, BALB-c and Swiss), and challenge strains (544 and 2308), inthe immunogenicity tests of S19 and RB51 vaccines. This experiment demonstrated that bothchallenge strains can be used in immunogenicity tests of S19 and RB51, as well as the three strains of mice; however the use of BALB-c requires more studies to stablish proper paramenters. These two first studies were carried out to standardize methodologies to conduct the third study that aimed to compare the biological properties (immunogenicity and residual virulence) and genotypic profile of eight S19 vaccines commercialized in Brazil with the reference S19 obtained from USDA. This study comproved that all S19 vaccines commercialized in Brazil show adequate biological properties when compared to the reference vaccine strain. In addition, we concluded that the group of S19 vaccines studied is genetically very homogenous. The last goal of this study was to evaluate the shedding of B. abortus in the milk of cows vaccinated with RB51. The milk of vaccinated animals was tested by culture and PCR up to 63 days after vacination and only one sample of milk was positive in PCR, on the first day after vaccination. Thus, the spread of RB51 by milk seems not to be a public health problem. Nevertheless the pasteurization of the milk from cows recently vaccinated with RB51 is highly recommended. In conclusion, Brazil has great tools to promove brucellosis control.